MEMBUKA PINTU DUNIA: EKSPLORASI TREN BISNIS PARIWISATA DI KABUPATEN LAMPUNG SELATAN DALAM PERSPEKTIF GLOBAL - Herinanto, Dwi; Gumanti, Miswan (LPPM UNIVERSITAS BINA INSAN, 2024)
The background to the study of global trends related to tourism and creative business in Lampung Province, Indonesia, emerges from the importance of understanding the global dynamics that affect the development of these sectors at the local level. The phenomenon of globalization has changed the landscape of the tourism industry and creative business significantly. By understanding global trends related to tourism and creative, the Province of Lampung can identify opportunities, overcome challenges, and develop appropriate strategies to increase competitiveness and strengthen the contribution of tourism sector and creative enterprises to economic growth and sustainable development. The city of Lampung Selatan offers a wide range of tourist products, ranging from natural beauty, such as beaches, mountains, and waterfalls, to cultural heritage, like temples and museums. This diversification allows tourists to enjoy a variety of experiences during tourist visits. Exploring tourism business trends in Lampung City in a global perspective requires a holistic and planned approach for local governments among them: analysis of global trends, strengthening tourism infrastructure, digital promotion, development of tourist packages, international partnerships, environmental and cultural preservation, investing in SDM training, as well as environment and cultural conservation.